“Freeze, Don’t Move”: How to Arrest a Suspect in Heart Failure – A Review on Available GRK2 Inhibitors - Sorriento, Daniela; Ciccarelli, Michele; Cipolletta, Ersilia; Trimarco, Bruno; Iaccarino, Guido (Frontiers in Cardiovascular Medicine, 2016)
Cardiovascular disease and heart failure still collect the largest toll of death in western societies and around the world. A growing number of molecular mechanisms represent possible targets for novel therapeutic strategies, in order to counteract the metabolic and structural changes observed in the failing heart. GRK2 is one of such targets for which experimental and clinical evidence have been established. Indeed, several strategies have been put in place in order to interface with the known GRK2 mechanisms of action in the failing heart. This review deals with results from basic and pre-clinical studies, showing different strategies to inhibit GRK2 in heart failure in vivo (bARK-ct gene therapy, treatment with gallein and treatment with paroxetine) and in vitro (RNA aptamer, RKIP and peptide-based inhibitors), either by inhibiting the catalytic activity of the kinase(“Freeze!”) or by preventing its shuttling within the cell (“Don’t Move!”). Here we review the peculiarity of each strategy as regard to the ability to interact with the multiple tasks of GRK2 and the perspective development for eventual clinical use.